Phytoplankton Species Composition, Distribution And Abundance In Kerian River Estuary, Malaysia - Samsudin, Shazana Mohamad (2011)
This study was conducted to characterize the health status of Kerian River estuary based on phytoplankton community and its implication to the river water quality. Five sampling stations were designated, and samples were collected from April 2008 to June 2009 during spring tide at low and high tide. The relationship of phytoplankton abundance and distribution toward nutrient concentration (nitrate, nitrite, ammonia and phosphate) and other environmental parameters such as dissolved oxygen, salinity, total suspended solid and water transparency were investigated based on the non-supervised Artificial Neural Network (ANN) and Pearson correlation analysis using the SPSS software version 16.0.